Range of Motion Therapy to Improve Physical Mobility in an Ischemic Stroke Patient: A Case Study - Fadlilah, Nur; Septianingrum, Yurike; Wijayanti, Lono; Soleha, Umdatus (International Journal of Health Concord, 2025)
Background: Stroke is a neurological disease caused by an occlusion or hypoperfusion in the cerebral blood vessels, leading to neurological deficits and resulting in disability or death. Objective: The purpose of this case study is to describe nursing care in addressing impaired physical mobility needs by implementing Range of Motion (ROM) exercises in stroke patients, from initial assessment to evaluation Methods: This study adopted a descriptive single-case study design and was reported in accordance with the CARE (Case Report) guideline. The sampling frame consisted of one postoperative orthopedic patient who met predefined inclusion criteria, namely stable vital signs, the ability to communicate and cooperate with examination procedures, and no contraindication to range-of-motion (ROM) exercises. Data were collected through interviews, physical examination, structured observation, and review of clinical records. Functional status and motor impairment were assessed using the standardized muscle strength grading scale (Medical Research Council [MRC] scale, 0–5), along with clinical monitoring sheets to document changes in movement capacity. The intervention protocol consisted of prescribed ROM exercises—including passive-assisted and active movement techniques—administered twice daily over the observation period, with progression based on clinical tolerance and patient feedback. Result: At baseline assessment, the patient demonstrated unilateral left-sided weakness, with muscle strength graded at 3/5 for both upper and lower extremities based on the Medical Research Council (MRC) scale, indicating movement against gravity but not resistance. After three consecutive days of prescribed ROM intervention, follow-up assessment showed improvement to 4/5 in both extremities, reflecting increased capability to move against moderate resistance. Measurements were conducted by the same trained clinician using the same standardized scale to enhance reliability, although potential subjective scoring bias inherent to manual muscle testing cannot be fully excluded. Conclusion: There was an increase in muscle strength between before and after the intervention. It is expected that ROM therapy can be applied as an intervention to overcome physical mobility impairment in stroke patients.